2022
DOI: 10.1039/c9cs00311h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light induced dearomatization reactions

Abstract: This review provides an overview of visible-light induced dearomatization reactions classified based on the manner in which aromaticity is disrupted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(96 citation statements)
references
References 125 publications
(139 reference statements)
0
96
0
Order By: Relevance
“…In this regard, the past few decades have witnessed the rapid development of photocatalysts that can harvest visible-light photons for organic transformations to produce high value-added chemicals. 1 Among them, porous organic polymers (POPs) outperform the commonly-used transition metal complexes because of their unique advantages including excellent stability, being metal-free, cost effectiveness, recyclability, tunable photophysical properties through synthetic control and so on. 2 Despite the flourishing advancements, the majority are restricted to oxidative transformations such as oxidative hydroxylation of arylboronic acids, oxidation of sulfides, oxidative coupling of amines, and oxidative C–H functionalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the past few decades have witnessed the rapid development of photocatalysts that can harvest visible-light photons for organic transformations to produce high value-added chemicals. 1 Among them, porous organic polymers (POPs) outperform the commonly-used transition metal complexes because of their unique advantages including excellent stability, being metal-free, cost effectiveness, recyclability, tunable photophysical properties through synthetic control and so on. 2 Despite the flourishing advancements, the majority are restricted to oxidative transformations such as oxidative hydroxylation of arylboronic acids, oxidation of sulfides, oxidative coupling of amines, and oxidative C–H functionalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Seidel's group reported the diphenyl phosphate (DPP)-catalyzed, microwave-assisted, redox-neutral annulation reaction between tertiary aminobenzaldehydes 1 and indoles 2 to construct indole-fused benzazepines 3 (Scheme 3). 10 For the first time, the vinylogous imines 4, in situ-generated via condensation, were proposed as hydride acceptors to initiate the cascade intramolecular [1,5]-HT/cyclization process where tertiary aminobenzaldehydes 1 and indoles 2 were used as dielec- trophile and dinucleophile reagents, respectively (Scheme 3, path b). Mechanistically, although the spirocyclic indolenines 6 were not mentioned in this work, we reason that a possible pathway involving such species still could not be ruled out (Scheme 3, path a).…”
Section: Vinylogous Imines As Hydride Acceptorsmentioning
confidence: 99%
“…Dearomatization of readily available planar aromatics has emerged as one of the most fundamental and attractive transformations in organic synthesis, allowing straightforward access to sophisticated three-dimensional molecules, especially natural products and pharmaceuticals. [1][2][3] The past several decades have witnessed the flourishing of elegant dearomatization chemistry, and a plethora of efficient methodologies were developed to achieve high value-added conversions. To date, many reviews on this subject have been reported that cover certain aspects such as visible-lightinduced dearomatization, 1a,f chiral phosphoric acid-catalyzed asymmetric dearomatization, 1d transition metal-catalyzed dearomatization, 1h-j,m,2a,d hypervalent iodine-mediated dearomatization, 3c-e multicomponent reaction-based dearomatization, 1e and applications of dearomatization in the synthesis of complex natural products.…”
Section: Introductionmentioning
confidence: 99%
“…Radical-to-polar crossover reactions—which intertwine single- and two-electron chemistry—have become an emerging synthetic tool to overcome the intrinsic limitations of traditional radical and polar chemistry, 9 especially due to the rapid development of photoredox chemistry. 10 Organofluorine motifs, owing to their unique reactivity, stability, and biological properties, have gained preeminent importance as building blocks in medicinal and agricultural chemistry. 11 a α-Trifluoromethylstyrene derivatives are versatile synthetic intermediates for the construction of gem -difluoroalkene compounds, attainable through radical-to-polar crossover manifolds under mild conditions.…”
Section: Introductionmentioning
confidence: 99%